Embracing Wonder and Curiosity: Transforming teacher practice through escape room design. Issue 2 (4th March 2019) - Martens, Sherry; Crawford, Kathryn
Abstract : An important aspect of bringing innovation to education is supporting children's own innovative thinking. Teachers are finding that escape room activities can provoke children's wonder and determination to pursue their curiosity, which builds a foundation for innovators of the future.